Efficacy of the prescription of physical activity in the obese child population (2015)
Objective To determine the effectiveness of prescribing physical activity to the population of overweight and obese children, in accordance with the levels of evidence.Methods To find literature pertaining to the intervention of physical activity in overweight and obese children. four electronic databases were used: Pubmed, Embase, Cochrane and Lilacs. The search was conducted with a cut-off date of June 2012. Randomized controlled clinical trials of intervention programs involving physical activity for both overweight and obese children were selected. Two independent researchers reviewed and evaluated the quality of the studies, and extracted intervention and result data.Results A total of 204 studies were identified. 19 randomized controlled studies which complied with inclusion and exclusion criteria were included. These studies evaluated the impact of physical activity among obese children and compared different types of intervention based on exercise and diet or both with the objective of reducing weight in obese children.Conclusions It is necessary to conduct studies on obese children with bigger sample sizes to determine the effects of the treatment, and more importantly, to devise comprehensive programs that include a structured exercise program complemented by a dietary program. Likewise, the development of public health policies that allow for the development of national programs for weight and obesity control in Colombian children and adults should be developed, taking into account that the causes of obesity are multiple, including social, familiar, metabolic, and dietary aspects.